Ultrasonographic Adrenal Gland Measurements in Healthy Yorkshire Terriers and Labrador Retrievers. (4th June 2012) - de, T.; Combes, A.; Bedu, A.‐S.; Pey, P.; Daminet, S.; Duchateau, L.; Saunders, J. H.
Summary An upper threshold of 7.4 mm for maximal adrenal gland diameter is commonly used to detect pituitary‐dependent hyperadrenocorticism ultrasonographically in dogs. There is a substantial overlap between adrenal gland diameter of healthy dogs and of those with pituitary‐dependent hyperadrenocorticism. The aim of this study is to determine the measurements of both adrenal glands, in particular, of the height at the caudal glandular pole in a longitudinal plane, in the Labrador retriever and Yorkshire terrier, two breeds widely represented in the population suspected of hyperadrenocorticism. Seventeen Labrador retrievers and 24 Yorkshire terriers considered healthy were included in the study. Adrenal gland measurements were taken on static images and comprised in measurements of the length in a longitudinal plane (L), of the height at the cranial (CrHLG) and caudal pole (CdHLG) in a longitudinal plane and in a transverse plane (CrHTR and CdHTR, respectively), and of the width at the cranial and caudal poles in a transverse plane (CrWTR and CdWTR, respectively). This study established new upper thresholds for the left and right height at the caudal pole measured in a longitudinal plane: 7.9 mm (left) and 9.5 mm (right) for the Labrador retrievers and 5.4 mm (left) and 6.7 mm (right) for the Yorkshire terriers. All the measurements were significantly different between the two breeds. There was a significant relationship between CdHTR and CdHLG, and the age of the dogs for both breeds.